1999
DOI: 10.1056/nejm199906103402303
|View full text |Cite
|
Sign up to set email alerts
|

A Serologic Marker of Paraneoplastic Limbic and Brain-Stem Encephalitis in Patients with Testicular Cancer

Abstract: The serum of patients with subacute limbic and brain-stem dysfunction and testicular cancer contains antibodies against a protein found in normal brain and in testicular tumors. Detection of these antibodies supports the paraneoplastic origin of the neurologic disorder and could be of diagnostic importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
211
0
9

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(226 citation statements)
references
References 19 publications
6
211
0
9
Order By: Relevance
“…Data base searches revealed that the predicted human MAP-1 protein shares extensive amino acid sequence similarity with two other human proteins (Fig. 1A), Ma1 (58%) (15) and Ma2 (47%) (16), suggesting that MAP-1 is a member of a gene family. Ma1 and Ma2 were both initially identified as antigens recognized by autoantibodies present in the sera of some patients with paraneoplastic neurological syndromes with underlying malignancy (breast, colon, parotid for Ma1, and testicular cancer for Ma2) (15,16).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Data base searches revealed that the predicted human MAP-1 protein shares extensive amino acid sequence similarity with two other human proteins (Fig. 1A), Ma1 (58%) (15) and Ma2 (47%) (16), suggesting that MAP-1 is a member of a gene family. Ma1 and Ma2 were both initially identified as antigens recognized by autoantibodies present in the sera of some patients with paraneoplastic neurological syndromes with underlying malignancy (breast, colon, parotid for Ma1, and testicular cancer for Ma2) (15,16).…”
Section: Resultsmentioning
confidence: 96%
“…10 g of total RNA from various cell lines was annealed with oligo(dT) [12][13][14][15][16][17][18] and reversed-transcribed using Moloney murine leukemia virus reverse transcriptase (Roche Molecular Biochemicals) for the synthesis of first strand cDNA. 2 l of the first strand cDNA was subjected to the following PCR conditions: Initial incubation at 94°C for 5 min, then 25 cycles of amplification (94°C for 1 min, 55°C for 1 min, and 72°C for 1 min), ending with a final extension step of 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…86,87 A number of other interesting, paraneoplastic manifestations may be seen in association with germ cell tumors, especially germinomas, including hypercalcemia, 86,88 hypoglycemia, 89 exophthalmos, 90,91 autoimmune hemolytic anemia (usually ovarian dermoids), ataxia telangiectasia, 86 and limbic encephalopathy. 92,93 Spermatocytic seminoma Spermatocytic seminoma may be confused with usual seminoma, a very important distinction from the clinical standpoint since spermatocytic seminomas virtually never metastasize (except for those with a rare complication mentioned below) and do not merit treatment apart from orchiectomy. [94][95][96][97] This tumor is limited to the male gonad and has a number of fascinating aspects.…”
Section: Germinomamentioning
confidence: 99%
“…Since the description of anti‐Hu antibodies in 1985,35 and following the identification of other highly specific onconeural antibodies in the serum of PNS patients,37, 38, 39, 40, 41, 42, 43 current hypotheses suggest an autoimmune origin in PNS 1. According to the location of the antigen, two types of antibodies have been described in these conditions: antibodies targeting cell membrane antigens or antibodies against intracellular antigens, being the latter defined as onconeural 44.…”
Section: Discussionmentioning
confidence: 99%